Analysis of Public Wellbeing as the Determinants of Income Distribution Disparity in North Sumatra in the 2002-2021 Period - Saing, Rhenata Novita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Income distribution disparity is one of the challenges in the economic development process in any Indonesian region, especially North Sumatra. The objective of this research is to analyze how public wellbeing serves as one of the determining factors for income distribution disparity in North Sumatra during the 2002-2021 period. This quantitative study uses the Two-Stage Least Squares (2SLS), whose result suggest that population and poverty do not significantly influence per capita GRDP and that Human Development Index (HDI) positively and significantly influences per capita GRDP. Further, public wellbeing, which was measured using per capita GRDP, positively and significantly affects income distribution disparity, confirming Kuznets’s inversed U hypothesis. The findings above imply the importance of government policies aimed at enhancing human resource quality through education and health and designing more effective poverty eradication programs to attain sustainable equitable economic development in North Sumatra.